2013
DOI: 10.1001/jamapediatrics.2013.2632
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bedsharing Activity on Breastfeeding Duration Among US Mothers

Abstract: Multiple factors were associated with breastfeeding, including bedsharing. Given the risk of sudden infant death syndrome related to bedsharing, multipronged strategies to promote breastfeeding should be developed and tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 21 publications
6
43
0
2
Order By: Relevance
“…Consistent with prior studies, we also observed an association between breastfeeding and higher rates of bedsharing. 14,2224 However, roomsharing was the most common usual sleep location, even among mothers who were exclusively breastfeeding. In addition, there was no indication that providing advice to room share without bedsharing negatively affected the likelihood of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior studies, we also observed an association between breastfeeding and higher rates of bedsharing. 14,2224 However, roomsharing was the most common usual sleep location, even among mothers who were exclusively breastfeeding. In addition, there was no indication that providing advice to room share without bedsharing negatively affected the likelihood of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…203 However, a more recent longitudinal study provides strong evidence that bedsharing promotes breastfeeding duration, with the greatest effect among frequent bed-sharers. 202 Another recent study has shown that, compared with mothers who roomshared without bed-sharing, mothers who bed-shared were more likely to report exclusive breastfeeding (adjusted OR: 2.46; 95% CI: 1.76-3.45) or partial breastfeeding (adjusted OR: 1.75; 95% CI: 1.33-2.31). 204 Although bed-sharing may facilitate breastfeeding, 175 there are other factors, such as intent, that influence successful breastfeeding.…”
Section: Figurementioning
confidence: 98%
“…Studies have found an association between bed-sharing and longer duration of breastfeeding, 202 but most of these were cross-sectional studies, which do not enable the determination of a temporal relationship: that is, whether bedsharing promotes breastfeeding or whether breastfeeding promotes bed-sharing, and whether women who prefer one practice are also likely to prefer the other. 203 However, a more recent longitudinal study provides strong evidence that bedsharing promotes breastfeeding duration, with the greatest effect among frequent bed-sharers.…”
Section: Figurementioning
confidence: 99%
“…80 Studies from England, the United States, and New Zealand have all reported a longer duration of breast feeding in infants who shared a bed. [81][82][83][84][85] In one US study, the reasons why African-American women chose to share a bed with their infants were no room for, or no money to buy, a cot, convenience of feeding (formula or breast milk), and ease of monitoring. 86…”
Section: Why Do Parents Choose To Bed Share?mentioning
confidence: 99%